2021
DOI: 10.3926/jotse.1109
|View full text |Cite
|
Sign up to set email alerts
|

Embarking digital learning due to COVID-19: Are teachers ready?

Abstract: The COVID 19 pandemic insists schools to close and embark on the digital environment to keep learning to happen. Implementing this learning in educational settings faces challenges related to human resources and infrastructure issues particularly in developing countries. This study investigated the teachers’ readiness in conducting digital learning in Yogyakarta, Indonesia. This exploratory study employed an online questionnaire and semi-structured interviews via either voice calls or video calls to safely gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 21 publications
(42 reference statements)
1
42
1
1
Order By: Relevance
“…Regardless of experience with digital modalities for teaching or a desire to move instruction online, educators around the world were forced to make a major shift in their instruction (Onyema et al, 2020 ). Similar to Aditya’s ( 2021 ) survey of 62 K-12 educators’ readiness to conduct digital learning in Indonesia, we found educators used both synchronous and asynchronous modalities of teaching online during emergency remote teaching. Figure 1 presents the types of digital tools that educators used during emergency remote teaching due to COVID-19 and their frequency of use.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Regardless of experience with digital modalities for teaching or a desire to move instruction online, educators around the world were forced to make a major shift in their instruction (Onyema et al, 2020 ). Similar to Aditya’s ( 2021 ) survey of 62 K-12 educators’ readiness to conduct digital learning in Indonesia, we found educators used both synchronous and asynchronous modalities of teaching online during emergency remote teaching. Figure 1 presents the types of digital tools that educators used during emergency remote teaching due to COVID-19 and their frequency of use.…”
Section: Resultssupporting
confidence: 78%
“…Less frequently, the technological tool, group chat (32%) was used. Aditya ( 2021 ) reported that most educators in Indonesia used online discussion during emergency remote teaching, however, specific synchronous tools were not discussed. Similar to the asynchronous tools, these tools allowed educators to interact with their students as if they were in class together.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations